Pigmented optic disc lesion: A melanoma masquerade - Zeba Muzammil Shaikh (TNOA Journal of Ophthalmic Science and Research, 2020)
A 67-year-old male was diagnosed with a pigmented lesion on the optic disc. Optic disc melanocytoma (ODM) is a rare benign, nonprogressive, heavily pigmented lesion arising from the melanocytes of the optic disc. The archetypal characteristics include dark pigmentation, feathery borders, and obscuration of the optic disc. It may be indistinguishable from choroidal melanoma occasionally. A regular follow-up with fundus photography is needed for early diagnosis of unusual complications.